Invariant cones and stability of linear dynamical systems - Aliluiko, A. M.; Mazko, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We present a method for the investigation of the stability and positivity of systems of linear differential equations of arbitrary order. Conditions for the invariance of classes of cones of circular and ellipsoidal types are established. We propose algebraic conditions for the exponential stability of linear positive systems based on the notion of maximal eigenpairs of a matrix polynomial.